After the Axes? The Rock Art at Copt Howe, North-west England, and the Neolithic Sequence at Great Langdale. (15th December 2019) - Bradley, Richard; Watson, Aaron; Style, Peter
Abstract : Within sight of the Neolithic axe quarries on the Langdale Pikes is a group of massive boulders at Copt Howe. The two largest command a direct view of the stone source where the sun sets into the mountainside at the midsummer solstice. Both are decorated by pecked motifs which resemble features of Irish passage tomb art. Small-scale excavation in 2018 showed that a rubble platform had been built at the foot of the main decorated surface and sealed two further motifs of similar character. New work has established an important sequence in Great Langdale. Recently obtained radiocarbon dates indicate that the main period of axe production was between 3800 and 3300 bc, whilst Irish megalithic art is later and was made between about 3300 and 2900 bc, suggesting that Copt Howe achieved its importance after axe-making had ceased or was in decline. That is consistent with an increasing emphasis on relations between northern Britain and Ireland during the Late Neolithic period. Perhaps Copt Howe itself was treated as a 'natural' passage tomb.